Data Acquisition System based on Serial Port - Chen, Peng (Journal of Theory and Practice of Engineering Science, 2024)
Data collection refers to the automatic collection of non electrical or electrical signals from sensors or other devices with analog or digital units under test, and then sent to the upper computer for analysis and processing. In recent years, people have been constantly paying attention to the development and market situation of data collection and its applications. The attention of the general public has led to a qualitative leap in the development of data collection systems, which are widely used in various digital markets. This article introduces the relevant concepts and basic principles of data collection, and designs the hardware and software implementation method and process of a data collection system based on STM32F103. After signal collection, it is converted into signals through ADC0832 and supplied to the microcontroller for data collection. RS-485 standard is used to communicate with the PC.